2002
DOI: 10.1086/339171
|View full text |Cite
|
Sign up to set email alerts
|

X‐Raying the Ultraluminous Infrared Starburst Galaxy and Broad Absorption Line QSO Markarian 231 withChandra

Abstract: With 40 ks of Chandra ACIS-S3 exposure, new information on both the starburst and QSO components of the X-ray emission of Markarian 231, an ultraluminous infrared galaxy and broad absorption line QSO, has been obtained. The bulk of the X-ray luminosity is emitted from an unresolved nuclear point source, and the spectrum is remarkably hard, with the majority of the flux emitted above 2 keV. Most notably, significant nuclear variability (a decrease of $45% in approximately 6 hr) at energies above 2 keV indicates… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
96
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 77 publications
(108 citation statements)
references
References 74 publications
(133 reference statements)
11
96
1
Order By: Relevance
“…The inferred densities [n(H 2 ) $ 10 4 cm À3 ] may explain the submillimeter CO emission detected by PIW07 and somewhat lower densities (a few ; 10 3 cm À3 ) can account for the [O i] line emission. We do not however rule out the possibility that some of the FIR emission arises from a more extended region, such as the outermost disk observed by DS98 in the millimeter CO lines or the much more extended region observed in soft X-rays (Gallagher et al 2002).…”
Section: Discussionmentioning
confidence: 79%
“…The inferred densities [n(H 2 ) $ 10 4 cm À3 ] may explain the submillimeter CO emission detected by PIW07 and somewhat lower densities (a few ; 10 3 cm À3 ) can account for the [O i] line emission. We do not however rule out the possibility that some of the FIR emission arises from a more extended region, such as the outermost disk observed by DS98 in the millimeter CO lines or the much more extended region observed in soft X-rays (Gallagher et al 2002).…”
Section: Discussionmentioning
confidence: 79%
“…This weak-line source may be a highredshift analogue of Mrk 231, a Compton thick AGN with a weak Fe K line in the local Universe (e.g., Braito et al 2004;Gallagher et al 2002;Iwasawa et al 2011, and other references therein). The large EW observed in PID 114 (Table 5) agrees with an Fe K line expected from a reflection-dominated spectrum from cold medium, giving a support to the possibility of a Compton thick source.…”
Section: -20 Kev Excess Sourcesmentioning
confidence: 95%
“…X-ray observations by ROSAT, ASCA (Turner 1999;Iwasawa 1999;Maloney & Reynolds 2000), and more recently Chandra (Gallagher et al 2002;Ptak et al 2003) have revealed the presence of extended soft X-ray emission with a thermal origin that is likely to be associated with the circumnuclear starburst and a hard and flat (Γ 0.7) powerlaw component, as well as an Fe K α emission line with EW ∼ 300 eV (the line was detected by ASCA but not by Chandra). From combined XMMNewton and BeppoSAX observations of MRK 231, Braito et al (2004) −0.25 ), a soft component fitted with two thermal plasma models with temperatures kT 0.33 keV and 0.99 keV, and narrow emission lines at 6.28 keV and 6.66 keV.…”
Section: Mrk 231mentioning
confidence: 99%